Effectiveness of Walking on a Physiological Variable (Hypertension) in a Class of Elderly (60-65) Years - SAYAD, Hadj; KOUTCHOUK, Sidi Mohamed (Journal of Human Sciences, 2020)
The study aims to highlight the importance of walking in controlling the complications resulting from high sugar and blood pressure in the elderly. For this purpose, we followed the experimental method. The sample of the study reached (40) individuals, the second study is the study of the use of the proposed walking program that positively affects some of the physical variables in the elderly, namely: Blood pressure and heart rate and weight.